Natural Killer Cells in Liver Disease and Hepatocellular Carcinoma and the NK Cell-Based Immunotherapy. (4th September 2018) - Liu, Pingyi; Chen, Lingling; Zhang, Haiyan
Abstract : Nature killer (NK) cells play a critical role in host innate and adaptive immune defense against viral infections and tumors. NK cells are enriched in liver hematopoietic cells with unique NK repertories and functions to safeguard liver cells against hepatitis virus infection or malignancy transformation. However, accumulating evidences were found that the NK cells were modulated by liver diseases and liver cancers including hepatocellular carcinoma (HCC) and showed impaired functions failing to activate the elimination of the viral-infected cells or tumor cells and were further involved in the pathogenesis of liver injury and inflammation. The full characterization of circulation and intrahepatic NK cell phenotype and function in liver disease and liver cancer has not only provided new insight into the disease pathogenesis but has also discovered new targets for developing new NK cell-based therapeutic strategies. This review will discuss and summarize the NK cell phenotypic and functional changes in liver disease and HCC, and the NK cell-based immunotherapy approaches and progresses for cancers including HCC will also be reviewed.